Complex treatment of invasive corticotropic pituitary macroadenoma - Case report - Obel, Michał; Nowicka, Emilia; Dzikowski, Piotr; Pietrzak, Zofia; Stefaniak, Martyna; Obel, Ewa (Journal of Education, Health and Sport, 2022)
Introduction: Cushing’s disease is a hypercortisolemic state caused by the excess secretion of corticotropin by the pituitary adenoma. Cushing’s disease is diagnosed on the basis of clinical and laboratory signs of hypercortisolemia and the presence of an MRI pituitary adenoma. Pituitary surgery represents the first-line therapy, but it is non-curative in one third of patients, requiring additional treatments. Second-line treatments include pharmacotherapy, pituitary radiotherapy and bilateral adrenalectomy. Case report: A 57-year-old patient with clinical symptoms of hypercortisolemia was admitted to the Endocrinology Clinic due to dizziness and headache. Laboratory tests and MRI confirmed Cushing’s disease caused by invasive pituitary macroadenoma. The tumor was not completely resected through the sphenoid sinus. Disease symptoms were remitted and hormone levels were stabilized. After 2 years, the underlying disease was relapsed. A second tumor removal operation was performed. The tumor was incompletely removed. The disease has progressed.. The patient was referred for stereotaxic CyberKnife radiotherapy. Conclusion: Cushing’s disease should be diagnosed and treated in a specialized endocrinology center, and the success of treatment depends on a multidisciplinary team of physicians consisting of an endocrinologist, neurosurgeon and neuroradiologist.About 50% of untreated patients die within 5 years of the disease due to complications of hypercortisolemia. Surgical treatment is effective in the case of microadenomas, while in the case of macroadenomas, it may turn out to be ineffective when the tumor is highly invasive. If subsequent surgeries are unsuccessful, treatment with radiotherapy or pharmacotherapy should be given.